Robust adaptive control of surge instability in constant speed centrifugal compressors using tube-MPC. Issue 1 (1st January 2017) - Taleb Ziabari, Masoud; Jahed-Motlagh, Mohammad Reza; Salahshoor, Karim; Ramezani, Amin; Moarefianpur, Ali
Abstract: Surge is one of the two dynamic instabilities that occur in centrifugal compressors and can pose severe safety issues to the compression system. This paper tries to investigate the active surge control methods in centrifugal compressors. To this end, Moore–Greitzer Compressor Model is used, which considers a close couple valve as the independent variable. Most of the existing active controllers require information about system characteristics and upper bound of disturbances. In designing a controller, it is assumed that some bounded external disturbances are applied to the compressor, but its upper bound is unknown. As such, the throttle valve and the compressor's characteristic are uncertain. In the proposed new active controller, a fuzzy system is used to approximate the compressor characteristic. Also, the adaptive control is used to estimate the openings of the throttle valve and the parameters of fuzzy system. Then, a robust controller is employed to find the appropriate gain in Tube-MPC to avoid the system disturbances. Finally, by simulating the compressor's behavior after applying the designed active controller, one can prove its efficiency and robustness to uncertainty in model and disturbance rejection.